AN ANALYSIS OF SMK MUHAMMADIYAH 3 STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXT - Afriliyah Ningsih; Novitri Novitri; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to find out and analyze the students’ difficulties in writing recount text at the first-year students of SMK Muhammadiyah 3 Terpadu Pekanbaru. The population of this research were the first-year students of SMK Muhammadiyah 3 Terpadu Pekanbaru. The sample of this research was X ADP class, consist of 30 students who have been selected using cluster random sampling technique. The data were collected by using writing test. The writing test were analyzed using ESL Profile Composition by Jacob (1981) through three raters. There are five aspects have been analyzed: content, organization, vocabulary, language use and mechanic. The findings of the research revealed that students got fair to poor and very poor level in content aspect, good to average and fair to poor level in organization and vocabulary aspects, and fair to poor level in language use and mechanics aspects. As the result of the research, it found that students have the difficulties in writing recount text for each aspects of writing especially in content, language use and mechanics aspects.Key Word: Analysis, Difficulties, Writing, Recount Text